2014
DOI: 10.1063/1.4866131
|View full text |Cite
|
Sign up to set email alerts
|

Ecological risk assessment of elemental pollution in sediment from Tunku Abdul Rahman National Park, Sabah

Abstract: Abstract. Eleven (11) surface sediment samples were collected from Tunku Abdul Rahman National Park, Sabah. The neutron activation analysis (NAA) and inductively coupled plasma-mass spectrometry (ICP-MS) techniques were applied for the determinations metal contents and their distributions in sediment samples. The results shown that Arsenic (As) concentrations are enriched at all sampling stations except for station TAR 09, with enrichment factor (EF) values ranged from 1.1 to 7.2. The elements such as Cd, Cr, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 16 publications
0
7
1
Order By: Relevance
“…Fe is the acceptable normalization element (Deely and Fergusson 1994;Elias and Gbadegesin, 2011;Elias et al, 2014;Kowalska et al, 2016;Bhutiani et al, 2017;Mazurek et al, 2017), hence it was used for the calculation of EF. Authors have variously reported that iron has the highest concentration among heavy metals in cassava mill effluents (Adejumo and Ola, 2011;Olorunfemi and Lolodi, 2011;Orhue et al, 2014;Omomowo et al, 2015).…”
Section: Enrichment Factormentioning
confidence: 99%
See 2 more Smart Citations
“…Fe is the acceptable normalization element (Deely and Fergusson 1994;Elias and Gbadegesin, 2011;Elias et al, 2014;Kowalska et al, 2016;Bhutiani et al, 2017;Mazurek et al, 2017), hence it was used for the calculation of EF. Authors have variously reported that iron has the highest concentration among heavy metals in cassava mill effluents (Adejumo and Ola, 2011;Olorunfemi and Lolodi, 2011;Orhue et al, 2014;Omomowo et al, 2015).…”
Section: Enrichment Factormentioning
confidence: 99%
“…Typically, iron has a relatively high natural concentration and is therefore not expected to be substantially enriched from anthropogenic sources (Bhutiani et al, 2017). EF is mathematically expressed based on the method previously described and used by Bhutiani et al (2017), Elias et al (2014), Tang et al (2014), El-Metwally et al (2017), Gasiorek et al (2017), Kowalska et al (2016).…”
Section: Enrichment Factormentioning
confidence: 99%
See 1 more Smart Citation
“…CD is the sum of all contamination factors, which provides information about total contamination in a particular sampling location (Singovszka et al, 2014;Bhutiani et al, 2017). Contamination degree is often expressed based on the formula previously described by Hakanson (1980) and have been applied by Bhutiani et al (2017), Uriah and Shehu (2014), Singovszka et al (2014), Soliman et al (2015), Todorova et al (2016), Ghaleno et al (2015), Fiori et al (2013), Karydas et al (2015), Zhu et al (2012), Elias et al (2014), Mohseni-Bandpei et al (2016), Swarnalatha et al (2013), Hassaan et al (2016), Vowotor et al (2014), Ghazaryan et al (2015), Qingjie et al (2008), Odukoya et al (2016).…”
Section: Pollution Load Assessment Modelmentioning
confidence: 99%
“…Specifically, pollution index and or/ contamination indices is an important tool for processing, analyzing, and conveying raw environmental information to decision makers, managers, technicians, environmentalist and the general public at large (Caeiro et al, 2005;Sarala andSabitha, 2012). 1980;Sutherland, 2000;Tijani et al, 2004;Yu et al, 2004;Qingjie et al, 2008;Wang et al, 2010Wang et al, , 2016Liang et al, 2011;Suresh et al, 2011;Yang et al 2011;Sarala and Sabitha, 2012;Zhu et al, 2012;Fiori et al, 2013;Swarnalatha et al, 2013;Elias et al, 2014;Jiang et al, 2014;Singovszka et al, 2014;Tang et al, 2014;Uriah and Shehu, 2014;Vowotor et al, 2014;Al-Anbari et al, 2015;Ghaleno et al, 2015;Ghazaryan et al, 2015;Karydas et al, 2015;Soliman et al, 2015;Hassaan et al, 2016;Mohseni-Bandpei et al, 2016;Todorova et al, 2016;Bhutiani et al, 2017). But information on pollution load of heavy metals resulting from the discharge of cassava mill effluents into the soil is scanty in literature.…”
mentioning
confidence: 99%